How is Translation Learning Through the Application of the Cooperative-Contrastive Model? - Rahima, Ade; Zahar, Erlina; Rahim, Arif; Hutabarat, Zuhri Saputra (Information Technology and Science (ITScience), 2024)
The present research aims to verify the implementation of a cooperative-contrastive model that can overcome students’ difficulties in translating texts from English into Indonesian. The study was conducted by a lecturer-researcher who involved 31 students who took Translation II subject. The duration of the research was two months and took place at the English Education program of Batanghari University. The main finding of the research is that the contrastive-cooperative model does not boast promising results in overcoming students' difficulties in translating texts from English into Indonesian. On the contrary, the approach lends itself to new problems in the students' translation. Hence, the lecturer-researcher tried to overcome the difficulties by training the students with some techniques, such as substitution, description, expansion, and transposition.